2016
DOI: 10.15835/nbha44210583
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Ultrastructural Characteristics of <i>Dumontinia tuberosa</i> (Bull.) L.M. Kohn from <i>Ranunculus ficaria </i>L.

Abstract: Dumontinia tuberosa fungus was observed in different stages of development growing on the roots of Ranunculus ficaria in Cluj-Napoca (Romania), over the course of several years. It is not frequently encountered, therefore, we decided that will be interesting to cultivate it on nutritive medium, and to use the morphological data and the colony’s characteristics to identify the fungus. The identity of the fungus was reaffirmed through a molecular analysis of sclerotium DNA sequences. A new favourable nutritive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Here we present new localities for two rare (Mircea et al 2016;Agnello et al 2018;Fokshei 2022) and previously presented ascomycete species, Dumontinia tuberosa (Bull.) L.M.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Here we present new localities for two rare (Mircea et al 2016;Agnello et al 2018;Fokshei 2022) and previously presented ascomycete species, Dumontinia tuberosa (Bull.) L.M.…”
Section: Introductionmentioning
confidence: 75%
“…SEM images were obtained by a Hitachi SU5000 scanning electron microscope. By comparing the accumulated data with the relevant literature (Inzenga 1869;Doğan & Kurt 2016;Kim et al 2009;Uzuhashi et al 2010;Medardi 2012;Agnello et al 2013;2018;Thompson 2013;Beug et al 2014;Mircea et al 2016;Altuntaş et al 2021) the samples were identified. The specimens are kept at the Biology Department, Kamil Özdağ Science Faculty, Karamanoğlu Mehmetbey University.…”
Section: Methodsmentioning
confidence: 99%